Staphylococcus aureus nasal colonization among dental health care workers in Northern Germany (StaphDent study) - Nadine Lerche; Silva Holtfreter; Birgit Walther; Torsten Semmler; Fawaz Al'Sholui; Stephanie J. Dancer; Georg Daeschlein; Nils-Olaf Hübner; Barbara M. Bröker; Roald Papke; Thomas Kohlmann; Romy Baguhl; et al. (Elsevier, 2021)
Methicillin-resistant Staphylococcus aureus (MRSA) can colonize dental patients and students, however, studies on the prevalence of MRSA and methicillin-susceptible S. aureus (MSSA) among dental health care workers (DHCW) including use of personal protective equipment (PPE) are scarce. We conducted an observational study (StaphDent study) to (I) determine the prevalence of MRSA and MSSA colonization in DHCW in the region of Mecklenburg Western-Pomerania, Germany, (II) resolve the S. aureus population structure to gain hints on possible transmission events between co-workers, and (III) clarify use of PPE. Nasal swabs were obtained from dentists (n = 149), dental assistants (n = 297) and other dental practice staff (n = 38). Clonal relatedness of MSSA isolates was investigated using spa typing and, in some cases, whole genome sequencing (WGS). PPE use was assessed by questionnaire. While 22.3% (108/485) of the participants were colonized with MSSA, MRSA was not detected. MSSA prevalence was not associated with size of dental practices, gender, age, or duration of employment. The identified 61 spa types grouped into 17 clonal complexes and four sequence types. Most spa types (n = 47) were identified only once. In ten dental practices one spa type occurred twice. WGS data analysis confirmed a close clonal relationship for 4/10 isolate pairs. PPE was regularly used by most dentists and assistants. To conclude, the failure to recover MRSA from DHCW reflects the low MRSA prevalence in this region. Widespread PPE use suggests adherence to routine hygiene protocols. Compared to other regional HCW MRSA rates the consequent usage of PPE seems to be protective.